INFLUENCE OF MUSCLE FATS ON THE QUALITY OF INTERMEDIATE MOISTURE - OBANU, ZAK A (Fishery Technology, 2017)
Chrysicthys nigrodigitatus with 12.95 fat having an iodine value of74.8 and a saponificationnumber o( 198.48 and Citharinus citherus containing only 3.25% fat with iodinevalue of 67.8 and a saponificationnumber of 145.86 were studied as examples of fattyand lean fishes respectively. The intermediate moisture (IM) products of both fish typescompared with normal cooked samples, were evaluated as of acceptable colour, odour,texure and juiciness but of inferior taste due to the glycerol impact. However, duringstorage at 30Â°C the IM products became increasingly less acceptable with the deterioration being greater in the fatty fish than in the lean fish, although the fatty IM fish wassuperior to the IM lean fish with regard to water retention and juiciness. Overall qualitydifferences were most apparent in colourand odour with the fatty IM fish beingworse. The fatty fish had also greater evolution of TEA-reactive carbonyl breakdown products of lipid oxidation which were subsequently used up in non-enzymic browningproducing the correspondingly darker fish colour and greater off odour.